Characterization of passive dosimeters in proton pencil beam scanning – A EURADOS intercomparison for mailed dosimetry audits in proton therapy centres. (February 2021) - De Saint-Hubert, M.; De Angelis, C.; Knežević, Ž.; Michalec, B.; Reniers, B.; Pyszka, E.; Stolarczyk, L.; Swakon, J.; Foltynska, G.; Wochnik, A.; Parisi, A.; Majer, M.; et al.
Highlights: EURADOS WG9 characterization of several passive detector systems in Proton Therapy. Unique study comparing luminescence detectors and alanine from three institutes. Alanine detectors demonstrated the lowest linear energy transfer (LET) dependence. Alanine detectors show the best dosimetric properties for implementation in auditing. Luminescence detectors require more extensive calibrations for mail auditing. Abstract: The lack of mailed dosimetry audits of proton therapy centres in Europe has encouraged researchers of EURADOS Working Group 9 (WG9) to compare response of several existing passive detector systems in therapeutic pencil beam scanning. Alanine Electron Paramagnetic Resonance dosimetry systems from 3 different institutes (ISS, Italy; UH, Belgium and IFJ PAN, Poland), nat LiF:Mg, Ti (MTS-N) and nat LiF:Mg, Cu, P (MCP-N) thermoluminescent dosimeters (TLDs), GD-352M radiophotoluminescent glass dosimeters (RPLGDs) and Al2 O3 :C optically stimulated dosimeters (OSLDs) were evaluate. Dosimeter repeatability, batch reproducibility and response in therapeutic Pencil Beam Scanning were verified for implementation as mail auditing system. Alanine detectors demonstrated the lowest linear energy transfer (LET) dependence with an agreement between measured and treatment planning system (TPS) dose below 1%. The OSLDs measured on average a 6.3% lower dose compared to TPS calculation, with no significant difference between varying modulations and ranges. Both GD-352M and MCP-N measured a lower dose than the TPS and luminescent response was dependent on the LET of the therapeutic proton beam. Thermoluminescent response of MTS-N was also found to be dependent on the LET and a higher dose than TPS was measured with the most pronounced increase of 11%. As alanine detectors are characterized by the lowest energy dependence for different parameters of therapeutic pencil beam scanning they are suitable candidates for mail auditing in proton therapy. The response of luminescence detector systems have shown promises even though more careful calibration and corrections are needed for its implementation as part of a mailed dosimetry audit system.